2020
DOI: 10.1038/s41467-020-17503-y
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 prevents the accumulation of R-loops and protects against transcription–replication collision events and DNA damage

Abstract: Proper chromatin function and maintenance of genomic stability depends on spatiotemporal coordination between the transcription and replication machinery. Loss of this coordination can lead to DNA damage from increased transcription-replication collision events. We report that deregulated transcription following BRD4 loss in cancer cells leads to the accumulation of RNA:DNA hybrids (R-loops) and collisions with the replication machinery causing replication stress and DNA damage. Whole genome BRD4 and γH2AX ChI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 82 publications
(133 reference statements)
7
93
0
Order By: Relevance
“…10 Interestingly, we also found DNA damage throughout the gene body of DNMT1 following BRD4 loss. 9 As R-loops are key regulators of DNMT targeting to chromatin with important roles in cancer progression and treatment, 4 our findings hint that combining DNMT inhibitors, or other novel therapies that exacerbate TRCs and replication stress-induced DNA damage, with bromodomain inhibitors, could increase their therapeutic potential for cancer treatment. These findings that TRCs, DNA damage, and cell death result from R-loop accumulation following BRD4 inhibition suggests that therapeutic induction of R-loop persistence could be a generalizable approach for inducing oncogenic cell death.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…10 Interestingly, we also found DNA damage throughout the gene body of DNMT1 following BRD4 loss. 9 As R-loops are key regulators of DNMT targeting to chromatin with important roles in cancer progression and treatment, 4 our findings hint that combining DNMT inhibitors, or other novel therapies that exacerbate TRCs and replication stress-induced DNA damage, with bromodomain inhibitors, could increase their therapeutic potential for cancer treatment. These findings that TRCs, DNA damage, and cell death result from R-loop accumulation following BRD4 inhibition suggests that therapeutic induction of R-loop persistence could be a generalizable approach for inducing oncogenic cell death.…”
mentioning
confidence: 86%
“…6 We and others recently reported that the epigenetic reader BRD4, plays a critical role in maintaining R-loop homeostasis and preventing TRCs in a subset of cancer cells. [7][8][9] BRD4 and other members of the bromodomain-containing family of proteins, including BRD2 and BRD3, are transcriptional coactivators that recognize acetylated lysine residues on histones directly via their conserved tandem bromodomains. BRD4 in particular, is enriched at enhancer regions of the MYC oncogene, leading to the development of bromodomain inhibitors as a treatment for Myc-driven cancers.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Under normal conditions, RNAPII is phosphorylated at serine 2 by cyclin-dependent kinase 9 (CDK9) in complex with BET bromodomain protein 4 (BRD4). This modification appears to be important to proceed with transcription and to prevent TRC and DNA breaks [65,66]. Chromatin remodeling complexes, such as the one of Mec1, INO80 and PAF1 in budding yeast, can prevent TRC by removing RNAPII [67]; INO80 depletion in prostate cancer cells leads to increased formation of R-loops [68].…”
Section: Formation Of Double-strand Breaks Is Provoked By Rnamentioning
confidence: 99%